Analisis Collaborative Office Space Dalam Upaya Peningkatan Kepuasan Kerja Karyawan Pada Divisi Business Development Rumah Sakit Siloam TB Simatupang - Sungkar, Jessica Valery; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Siloam Hospital is a healthcare provider company under the auspices of Lippo Group. One of the branches of Siloam Hospital is located on Jalan TB Simatupang, South Jakarta. In the business development division of Siloam TB Simatupang Hospitals, South Jakarta, it is known that there are employee job satisfaction problems seen from the absenteeism level which has decreased over the last few years.The aim of this research is to determine the effect of collaborative office space, consist of tangible and intangible aspect, to employee job satisfaction in business development division at Siloam Hospitals, Jakarta. The type of this research is explanatory research, with 40 respondents of samples. Used questionnaire as data collecting with Semantic Differential scale. In the data analysis method used is test of validity and reliability, correlation coefficient (R), regression test, coefficient of determination (R2), significance of t test and F test by using SPSS 16.0The results of this research indicate that the tangible and intangible aspects of the collaborative office space have a significant influence on employee job satisfaction division business development Siloam TB Simatupang Hospital Jakarta. The two variables are tested in stages and both show that tangible aspect (0,662) and intangible aspect (0.403) have strong and pretty much strong relationship to job satisfaction of business development division employee of Siloam TB Simatupang Jakarta Hospital. The amount of donation possessed by tangible aspect variables in the collaborative office space is bigger rather than the intangible aspects of the collaborative office space. The coefficient of determination (R2) for tangible aspect variable in collaborative office space is 43,9% and intangible aspect in collaborative office space is 16,2%.Company is suggested to keep tangible aspect in colaborative office space good and also develop the tangible aspect, so that job satisfaction of employees keeps imrpoved. The same thing going to the intangible aspect, it is necessary to improve and maximize communication and interaction among employees.